Analisis Store Atmosphere Dan Kualitas Pelayanan Berdasarkan Persepsi Pelanggan - Candra Kartika Putri; Sujoko (FEB Universitas Maritim Semarang, 2022)
Abstract. This study aim is to find out how customers feel about the atmosphere and quality of service at Sociostyle Stores. A descriptive quantitative method was used in this study. In this study, the study population was made up of people who shopped at the Temanggung Sociostyle Shop. The exact number of people who shopped there was not known because the number of people who shopped there was always growing. Because of this, the sampling strategy is based on the Lemeshow formula. Based on the numbers, the number of people in the sample is 100. For their research, the researchers used a questionnaire with a Likert scale and direct observation. After the data were collected, the instrument's validity and reliability were checked. After the instrument has been found to be valid and trustworthy, descriptive statistical analysis can continue so that the research questions can be answered. The results showed that all of the store atmosphere and service quality variables were in the very high category because their mean values were between 3.24 and 4.00.